Wastewater treatment by microalgae - Plöhn Martin; Spain Olivia; Sirin Sema; Silva Mario; Escudero-Oñate Carlos; Ferrando-Climent Laura; Allahverdiyeva Yagut; Funk Christiane (WILEY, 2022)
The growth of the world's population increases the demand for fresh water, food, energy, and technology, which in turn leads to increasing amount of wastewater, produced both by domestic and industrial sources. These different wastewaters contain a wide variety of organic and inorganic compounds which can cause tremendous environmental problems if released untreated. Traditional treatment systems are usually expensive, energy demanding and are often still incapable of solving all challenges presented by the produced wastewaters. Microalgae are promising candidates for wastewater reclamation as they are capable of reducing the amount of nitrogen and phosphate as well as other toxic compounds including heavy metals or pharmaceuticals. Compared to the traditional systems, photosynthetic microalgae require less energy input since they use sunlight as their energy source, and at the same time lower the carbon footprint of the overall reclamation process. This mini-review focuses on recent advances in wastewater reclamation using microalgae. The most common microalgal strains used for this purpose are described as well as the challenges of using wastewater from different origins. We also describe the impact of climate with a particular focus on a Nordic climate.